Facing Trauma and Surgical Emergency in Space: Hemorrhagic Shock - Pantalone, D.; Chiara, O.; Henry, S.; Cimbanassi, S.; Gupta, S.; Scalea, T. (Frontiers in Bioengineering and Biotechnology, 2022)
Although the risk of trauma in space is low, unpredictable events can occur that may require surgical treatment. Hemorrhage can be a life-threatening condition while traveling to another planet and after landing on it. These exploration missions call for a different approach than rapid return to Earth, which is the policy currently adopted on the International Space Station (ISS) in low Earth orbit (LEO). Consequences are difficult to predict, given the still scarce knowledge of human physiology in such environments, except for blood loss that in space can deplete the physiological reserves of the affected astronaut and also the stored reserve of the crew as well. In this review, we will describe different aspects of hemorrhage in space and by comparison with terrestrial conditions, the possible solutions to be adopted, as well as the current state of the art.